Reliability assessment of restructured power systems using optimal load shedding technique - Wang, Peng (2011)
Power systemrestructuring and deregulation has changed the strategy of reliabilitymanagement of a power system. Load shedding, and generation and reserve re-dispatch methods used in the existing reliability evaluation techniques have to be improved to incorporate these changes. An optimisation technique, incorporating those changes, is proposed in this study to determine load curtailment and generation re-dispatch for each contingency state in the reliability evaluation of restructured power systems with the Poolco market structure. The problem is formulated using the optimal power flow (OPF) technique. The objective of the problem is to minimise the total system cost, which includes generation, reserve and interruption costs, subject to market and network constraints. A model for the contingency management of a Poolco power market is presented to include generation and reserve biddings, reliability considerations and transmission network constraints in reliability evaluation. Both supply side reliability for a generation company (Genco) and demand-side reliability for a customer can be calculated using the technique. The proposed technique can be used to evaluate both conventional and restructured power systems, and can provide both economic and reliability information for the independent